Um caso especial - o conhecimento da atitude do esquisso considerando os desenhos produzidos por indivíduos com a síndrome savant - Duarte, Miguel Bandeira, 1970- (2018)
The comparison of qualities between drawings, currently practiced in the research process, allow us to find unusual approaches that seek to clarify the main issues. This article aims to compare common sketches with the drawings produced by individuals with the savant syndrome. In the observation drawing paradigma, similar graphic qualities clarify the relation between observation, memorization and representation, between the direct perception and the use of symbolic structures